1999
DOI: 10.1366/0003702991947397
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Determination of Borophosphosilicate Glass Thin-Film Properties Using Infrared Emission Spectroscopy

Abstract: We have completed an experimental study to investigate the use of infrared emission spectroscopy (IRES) for the quantitative analysis of borophosphosilicate glass (BPSG) thin films on silicon monitor wafers. Experimental parameters investigated included temperatures within the range used in the microelectronics industry to produce these films so that the potential for using the IRES technique for real-time monitoring of the film deposition process could be evaluated. The film properties that were investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 15 publications
(8 reference statements)
0
14
0
Order By: Relevance
“…16 The temperature variations were ascribed to lack of reproducible contact between the sample and the heater and/or the sample and the thermocouple when placing a sample in the emission apparatus. The temperature variations are potentially a significant source of error in the measurement of film properties on product wafers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 The temperature variations were ascribed to lack of reproducible contact between the sample and the heater and/or the sample and the thermocouple when placing a sample in the emission apparatus. The temperature variations are potentially a significant source of error in the measurement of film properties on product wafers.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently shown that nondestructive determination of thin-lm dielectric properties on monitor wafers can be m ade with the use of infrared emission spectroscopy (IRES). [13][14][15][16] These experiments illustrated that although IR emission data collected from BPSG thin-lm samples are complicated, it is possible to collect highly precise spectra on a time scale that is fast relative to the CVD process. Multivariate analysis methods applied to these spectra then provide rapid m easurements of B content, P content, lm temperature, and lm thickness.…”
Section: Introductionmentioning
confidence: 99%
“…Determination of the phosphorus content in soil, 1 glass 2 and phosphorus – containing compounds has been extensively evaluated by spectrophotometric methods. 3 , 4 The phosphorus capacities of orthophosphates, condensed phosphates, and phosphorus ligands bound to organic polymers can be measured using the vanadate-molybdate reagent.…”
Section: Introductionmentioning
confidence: 99%
“…Fourier transform infra-red spectroscopy (FTIR) [14][15][16][17], infra-red external reflection absorption spectroscopy (IRRAS) [18] and infra-red emission spectroscopy (IRES) [19] have all been used to analyze for boron and phosphorous content in BPSG. These infra-red spectroscopic techniques give valuable structural information in addition to compositional analysis but, unfortunately the wavelengths involved limit their ability to target and analyze particular regions of planar waveguide structures.…”
Section: Introductionmentioning
confidence: 99%